Re-framing Common Themes in Religions and Development Research - Wilkinson, Olivia (2022)
Religions and development research over the last twenty years has centered around some major common themes: that religions matter but are side-lined or ignored; that there are surges of interest in religions from international development policy makers and practitioners but that these can lead to instrumentalization and unfair co-option of religious assets; and multiple definitions and categorizations of faith-based organizations. While these major themes have advanced the field previously, new and recent emerging themes update and re-frame these previously dominant debates. The analysis in this article finds that the new emerging themes push for engaging with the complexity and contextuality of religions, working with a fuller diversity of religious actors, and using a range of research methods. Ultimately, the article finds that researchers in religions and development can move beyond questions of “added value” of religions to development, and instead focus on the nuance of religions for development goals in contextually specific ways.
Keywords: faith-based organizations; faith actors; Faith; humanitarian; international development; Religions